The Art Institute of Chicago : Museum Studies. (Chicago : The Art Institute of Chicago, 1966)
Museum Studies offers readers in-depth explorations of the Art Institute's rich collections, history, and special exhibitions. (Jstor)
Online: https://www.jstor.org/journal/artinstchicmuses
Engels
Tijdschriften
Keywords: The Art Institute of Chicago